KOMUNIKASI INTERPERSONAL GURU DALAM MENINGKATKAN KEPERCAYAAN SISWA PADA BIMBINGAN BELAJAR ONMA DI KOTA BENGKULU - Sapta Sari (UNIVED PRESS, Universitas Dehasen Bengkulu, 2018)
The development of tutoring or bimbel does not only occur in big cities but also in the city of Bengkulu. Like Primagama, Ganesha, Talenta, and Onma. One of the tutoring in Bengkulu City is Onma. Onma Foundation is an institution that aims to help the government to realize a society that has competitive value in the world of education and the labor market, especially in Bengkulu Province. Up to now the addressable guidance institution on Mayjend street. Soetoyo No. 25 Tanah Patah Sub-District of Bengkulu City is still one of the partners of the Provincial Government and the City of Bengkulu to realize Bengkulu City Students. The ability and trust of students studying at Onma is influenced by the quality of the teacher. Teachers who are confident and have good interpersonal communication with their students will make students more quickly master the subject matter and they also have confidence in themselves that they are able to complete the tasks given by the teacher in tutoring. In this case, the teacher plays a very important role in increasing students' trust in their guidance teacher. Given that there are still many high school students in the city of Bengkulu not yet fully have good beliefs and morals even though in the field of academic achievement they excel, like Public High School 05 City students Bengkulu. The purpose of this study was to examine the process of tutoring for students through interpersonal communication between teachers and students which has a relationship with the level of trust possessed by high school students 05 City of Bengkulu who are currently attending the tutoring process at Onma Bengkulu.